Secondary education and international labor mobility: Evidence from the natural experiment in the Philippines - Yoko Sakai; Kazuya Masuda (IZA Journal of Development and Migration, 2020)
International labor mobility is a key factor for a well-functioning labor market. Although educational attainment is known to affect regional labor mobility within a country, evidence of a relationship between schooling and international labor mobility is limited, particularly in developing countries. This study uses the across-cohort variation in the exposure to the 1988 free secondary education reform in the Philippines to examine the impact of years of education on the propensity of working abroad. The results suggest that free secondary education increased the years of education for men. Moreover, the additional years of education reduced the likelihood of working abroad by 3.2% points on average. However, an extra year of female education was not associated with the probability of working abroad. These results indicate that a program for improving access to secondary education may affect international labor mobility for men even after a few decades. It underscores the importance of considering the possible labor market consequences when designing the education reform in developing countries.
Keywords: J61; R23; I20; 330; labor mobility; migration; education; Philippines; free secondary education